Waste Minimization in Construction Using Building Information Modeling (BIM) Approach - Jia Yi, Chen; Seow, Ta Wee; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Construction waste is no longer a new problem in the construction industry.This is due to the rapid development of the construction industry, which has becomea serious problem. Implementing the building information model (BIM) can minimizewaste, but BIM is not a popular method for waste minimization in Malaysia. BIM isdefined as a digital representation of the physical and functional characteristics of afacility and it is used to integrate data collection, exchange, and visualization duringthe life cycle of a construction project. This study aims to determine the currentimplementation of BIM in minimizing construction waste and study the perception ofcontractors in the challenge of implementing BIM in minimizing waste. The scopearea of the study will focus on contractors and construction companies in the KualaLumpur area. By the way, this study uses a qualitative method to get the requiredinformation and there are 11 respondents will be interviewed. After collecting all theinformation, analysis of the information collected from the interview will be carriedout. The finding of this study, the current implementation of BIM in minimizing wasteis still low and the main challenges faced by construction players can be divided intothree categories, which are process, people, and technology. In conclusion, theresearch objectives are achieved and the research study will help to develop theknowledge on the BIM in minimizing waste. So that encourages people to implementBIM in the project and push the Malaysia construction industry into a higher path.